2013
DOI: 10.1108/gs-06-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Grey relational analysis between energy consumption and economic growth

Abstract: Purpose -The relationship between energy consumption (EC) and economic growth is a well-known and more studied subject in literature. In this study, Turkey's EC and gross domestic product (GDP) relation is analyzed. The aim of this study is to find out the relative importance of energy components on GDP for Turkey. Hence, the authors can make some strategic implications up to the importance of energy components on GDP. Design/methodology/approach -In this study, two methods are used to find out the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Pai et al applied grey relation analysis to evaluate the effects of transportation activities on air quality variations in Japan from 1974 to 2004 [ 26 ]. In the study of [ 27 ], Turkey’s EC and gross domestic product (GDP) relation was analyzed. The relative importance of energy components on GDP for Turkey were found out.…”
Section: Methodsmentioning
confidence: 99%
“…Pai et al applied grey relation analysis to evaluate the effects of transportation activities on air quality variations in Japan from 1974 to 2004 [ 26 ]. In the study of [ 27 ], Turkey’s EC and gross domestic product (GDP) relation was analyzed. The relative importance of energy components on GDP for Turkey were found out.…”
Section: Methodsmentioning
confidence: 99%
“…Then k represents the number of evaluation indexes, and j represents the number of dimensionless and weight combination schemes. The variance of each combination scheme can be calculated by (22).…”
Section: The Objective Weight Optimization Model Based Onmentioning
confidence: 99%
“…The steps of grey relational model are as follows [22,23]. First, the optimal value of each index is selected as the reference sequence C 0 .…”
Section: Comprehensive Evaluation Model Of Clean Energy Development Lmentioning
confidence: 99%
“…After the assessment indicator weights were achieved, gray relational analysis was used to evaluate mine safety. Gray relational analysis is an important part of gray system theory [ 32 ], which has become very popular in many areas, such as green supplier selection [ 33 ], energy consumption, economic growth [ 34 ], and decision-making [ 35 ]. The relative importance of energy components on gross domestic product for Turkey had been obtained based on gray relational analysis, and the results showed that the most important energy sources for Turkey were oil and renewables [ 34 ].…”
Section: Introductionmentioning
confidence: 99%